Biosynthesis, Characterization, and Evaluation of the Therapeutic Potential of Zinc Oxide Nanoparticles - Al Sahlanee, Rasha; Ibrahim, Abdulrahman K. (Iraqi Journal of Science, 2025)
This research aimed to produce Zinc Oxide nanoparticles using bacterial isolates and examine their potent antibacterial properties and toxic effects on breast cancer cell. A clinical isolate of Pseudomonas aeruginosa was selected from 170 clinical bacterial isolates for the biosynthesis of nanoparticles. ZnO NPs were biosynthesized from the bacterial filtrate. The physiochemical properties of the synthesized ZnO NPs were then characterized using various techniques including UV–vis spectroscopy, Atomic Force Microscope (AFM), Fourier Transform Infrared (FTIR), Energy Dispersive Spectroscopy (EDS) and Field Emission Scanning Electron Microscopy (FESEM). The antibacterial tests were conducted using the agar well diffusion technique, employing ZnO NPs at concentrations ranging from 3.125 to 100 µg/ml. Additionally, the anticancer effects on MCF-7 breast cancer cells were examined using the MTT assay. The study also included an assessment of apoptotic activity using Annexin V, analyzed through flow cytometry. From FESEM analysis, ZnO NPs were found to have an average size of 32.5 nm. and the other characteristic analysis confirmed the production of nanoparticles. The activity of produces ZnO NPs was tested against three pathogens (Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa) in solid media. ZnO NPs showed potential antibacterial activity against tested bacteria, at concentration 100 µg/ml of ZnO NPs which showed the highest inhibition zones were (28, 27 and 23mm ) for S. aureus , E. coli  and P. aeuroginosa respectively , Whereas the lowest  inhibition zones were observed at 3.125 µg/ml  for the S. auereus and E.coli by diameter ( 9 and 10 mm) respectively and with no effect on P. aeuroginosa. These nanoparticles also showed a dose response anticancer activity against MCF-7 cells with IC50 72.87µg ml-1 while on normal HEF cell line showed less effective. Annexin-V / Propidium Iodide (PI) flow cytometry analysis confirmed that ZnO NPs induce apoptosis in MCF-7 cells.